A comparison of adolescent penetrating trauma patients managed at pediatric versus adult trauma centers in a mature trauma system. Issue 6 (June 2020) - Rogers, Frederick B.; Horst, Michael A.; Morgan, Madison E.; Vernon, Tawnya M.; Gaines, Barbara A.; Rogers, Amelia T.; Gross, Brian W.; Cook, Alan D.; Bradburn, Eric H.
Abstract : BACKGROUND: While there is little debate that pediatric trauma centers (PTC) are uniquely equipped to manage pediatric trauma patients, the extent to which adolescents benefit from treatment there remains controversial. We sought to elucidate differences in management approach and outcome between PTC and adult trauma centers (ATC) for the adolescent penetrating trauma population. We hypothesized that improved mortality would be observed at ATC for this subset of patients. METHODS: Adolescent patients (age, 15–18 years), presenting to Pennsylvania-accredited trauma centers between 2003 and 2017 with penetrating injury, were queried from the Pennsylvania Trauma Outcome Study database. Dead on arrival, transfer patients, and those admitted to a Level III or Level IV trauma center were excluded from analysis. Patient length of stay, number of complications, surgical intervention, and mortality were compared between ATC and PTC. Multilevel mixed effects logistic regression models with trauma center as the clustering variable were used to assess the impact of center type (ATC/PTC) on management approach and mortality adjusted for appropriate covariates. RESULTS: A total of 2, 630 adolescent patients met inclusion criteria (PTC: n = 428 [16.3%]; ATC: n = 2, 202 [83.7%]). Pediatric trauma centers had a lower adjusted odds of mortality (adjusted odds ratio [AOR], 0.35; 95% confidence interval [CI], 0.17–0.74; p = 0.006) and a lower adjusted odds of surgery (AOR, 0.67; 95% CI, 0.0.48–0.93; p = 0.016) than their ATC counterparts. There were no differences in complication rates (AOR, 0.94; 95% CI, 0.57–1.55; p = 0.793) or length of stay longer than 4 days (AOR, 0.95; 95% CI, 0.61–1.48; p = 0.812) between the PTCs and ATCs. There were also differences in penetrating injury type between PTC and ATC. CONCLUSION: The adolescent penetrating trauma patient population treated at PTC had less surgery performed with improved mortality compared with ATC. LEVEL OF EVIDENCE: Therapeutic, Level IV.